Validation of the Listeria Right NowTM Test for Detection of Listeria spp. from Selected Environmental Surfaces Without Enrichment. (23rd November 2019) - Le, Quynh-Nhi; Alles, Susan; Roman, Brooke; Tovar, Eric; Hosking, Edan; Zhang, Lei; Biswas, Preetha; Bastin, Benjamin; Bird, Patrick M; Mozola, Mark; Donofrio, Robert; Chen, Yi; et al.
Abstract: Background: Listeria Right Now TM is a novel, enrichment-free molecular method for detection of Listeria spp. in swab samples from environmental surfaces. The test provides results in real time, indicating the current or recent presence of Listeria spp. in the environment. After sampling, the entire contents of the swab are subject to sample processing, releasing large quantities of target ribosomal RNA molecules into the lysate. A portion of the lysate is then tested using the ANSR ® for Listeria isothermal nucleic acid amplification assay. Objective: A Performance Tested Method SM study was conducted to validate the method for detection of Listeria spp. in swab samples from stainless steel and sealed concrete surfaces. Methods and Results: In inclusivity testing, 60 of 60 Listeria spp. strains tested positive. In exclusivity testing, 31 of 31 nontarget bacterial strains tested negative. In LOD testing, the test was able to detect as few as 2 CFU of L. monocytogenes applied to a stainless steel surface. In matrix testing of inoculated stainless steel and sealed concrete surfaces, there were no statistically significant differences in method performance comparing the Listeria Right Now and U.S. Food and Drug Administration Bacteriological Analytical Manual reference culture procedures as determined by probability of detection analysis. In robustness testing, modest changes to three assay operating parameters simultaneously did not significantly affect performance of the test. Conclusions and Highlights: Results can be obtained in less than 1 h using the Listeria Right Now test, allowing food industry personnel to take immediate corrective action in the case of Listeria contamination incidents.